2015
DOI: 10.1155/2015/986895
|View full text |Cite
|
Sign up to set email alerts
|

The Increase of Intra-Abdominal Pressure Can Affect Intraocular Pressure

Abstract: Objective. This study aims to explore the usage of intraocular pressure measurements as the early indicator of the increase in intra-abdominal pressure. Methods. In this prospective study, 40 patients undergoing elective surgery were included. Patients were divided into four groups of 10 patients. The control group (Group C) was not subjected to laparoscopic intervention. Laparoscopic surgery was, respectively, performed with an intra-abdominal pressure of 9, 12, and 15 mmHg in Groups L (low), M (medium), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The aetiology of the elevated IOP in obese individuals may be due to increased intra-abdominal pressure causing increased episcleral venous pressure and choroidal vascular congestion (Ece et al 2015) or increased orbital fat causing episcleral venous compression (Lam et al 2016). Stojanov et al (2013) found significantly higher mean retrobulbar adipose tissue volume in obese subjects compared to normal-weight individuals using magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of the elevated IOP in obese individuals may be due to increased intra-abdominal pressure causing increased episcleral venous pressure and choroidal vascular congestion (Ece et al 2015) or increased orbital fat causing episcleral venous compression (Lam et al 2016). Stojanov et al (2013) found significantly higher mean retrobulbar adipose tissue volume in obese subjects compared to normal-weight individuals using magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-abdominal insufflation of carbon dioxide is the most widely used technique for creating working space during laparoscopy. It is important to keep the abdominal pressure under 12 mmHg because IAP greater than 12 mmHg may cause pathological changes in the cardiovascular system, hemodynamic parameters, pulmonary system, and renal function [14]. It has been known that increase of IAP causes a reduction in splanchnic blood flow resulting in biochemical evidence of oxidative stress and histological evidence of tissue injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…This can hypothetically be attributed to the intra-abdominal pressures used in the current study. When Ece et al (2015) studied the IOP in artificially ventilated humans undergoing laparoscopy, three different intra-abdominal pressures (9, 12 and 15 mmHg) were used. Ventilation was maintained by f R 10-12/min, V T 8-20 ml/kg, PEEP 3 cmH 2 O and EtCO 2 35 to 40 mmHg.…”
Section: Parametermentioning
confidence: 99%